Environmental pH and the Requirement for the Extrinsic Proteins of Photosystem II in the Function of Cyanobacterial Photosynthesis - Morris, Jaz N.; Eaton-Rye, Julian J.; Summerfield, Tina C. (Frontiers in Plant Science, 2016)
In one of the final stages of cyanobacterial Photosystem II (PS II) assembly, binding of up to four extrinsic proteins to PS II stabilizes the oxygen-evolving complex (OEC). Growth of cyanobacterial mutants deficient in certain combinations of these thylakoid-lumen-associated polypeptides is sensitive to changes in environmental pH, despite the physical separation of the membrane-embedded PS II complex from the external environment. In this perspective we discuss the effect of environmental pH on OEC function and photoautotrophic growth in cyanobacteria with reference to pH-sensitive PS II mutants lacking extrinsic proteins. We consider the possibilities that, compared to pH 10.0, pH 7.5 increases susceptibility to PS II-generated reactive oxygen species (ROS) causing photoinhibition and reducing PS II assembly in some mutants, and that perturbations to channels in the lumenal regions of PS II might alter the accessibility of water to the active site as well as egress of oxygen and protons to the thylakoid lumen. Reduced levels of PS II in these mutants, and reduced OEC activity arising from the disruption of substrate/product channels, could reduce the trans-thylakoid pH gradient (ΔpH), leading to the impairment of photosynthesis. Growth of some PS II mutants at pH 7.5 can be rescued by elevating CO2 levels, suggesting that the pH-sensitive phenotype might primarily be an indirect result of back-pressure in the electron transport chain that results in heightened production of ROS by the impaired photosystem.